2007
DOI: 10.1111/j.1365-3083.2007.01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochip Array‐based Analysis of Plasma Cytokines in HIV Patients with Immunological and Virological Discordance

Abstract: Assessment of cytokines in body fluids or cells provides important information in understanding the disease process and designing treatment strategies. Recent introduction of antibody‐based protein arrays have provided investigators simultaneous and specific detection of multiple analytes in a single sample using minimum volumes. In this study, we used a biochip array system capable of measuring 12 cytokines and growth factors (IL‐2, IL‐4, IL‐6, IL‐8, IL‐10, IL‐1α, IL‐1β, IFN‐γ, TNF‐α, monocyte chemoattractant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…49 Although HIV infection is immunosuppressive, cross-sectional studies showing that serum TNF-α is often raised in HIV-positive subjects in comparison with healthy control groups, indicate that the production of inflammatory cytokines is possible in the context of HIV. 30,31,35,50,51 Aukrust et al 52 also found significantly raised serum levels of soluble TNF receptors (sTNFRs) and a correlation between positive STNFRs and patient survival, which may make the level of serum sTNFRs a more useful measurement of TNF activity in patients with HIV infection than the serum concentration of TNF itself.…”
Section: An Altered Cytokine Environment In Hiv-positive Subjects Maymentioning
confidence: 93%
“…49 Although HIV infection is immunosuppressive, cross-sectional studies showing that serum TNF-α is often raised in HIV-positive subjects in comparison with healthy control groups, indicate that the production of inflammatory cytokines is possible in the context of HIV. 30,31,35,50,51 Aukrust et al 52 also found significantly raised serum levels of soluble TNF receptors (sTNFRs) and a correlation between positive STNFRs and patient survival, which may make the level of serum sTNFRs a more useful measurement of TNF activity in patients with HIV infection than the serum concentration of TNF itself.…”
Section: An Altered Cytokine Environment In Hiv-positive Subjects Maymentioning
confidence: 93%
“…Though there are differences in disease progression in both the groups investigated, it may be likely that the discordant patients perhaps had delayed initiation of HAART, as early treatment is reported to effectively restore PDC and CD4 T cell counts (40,41). Earlier, we had shown that the plasma cytokine milieu of discordant patients is associated with elevated levels of cytokines, such as vascular endothelial growth factor, epidermal growth factor, IL-1␣, and IL-1␤, which are reflective of the primary immune damage inflicted by high levels of HIV-1 replication in these individuals before the initiation of HAART (35). Therefore, it is likely that initial immune damage caused to the lymphoid tissue during primary HIV-1 infection affects recovery of CD4 T cells and PDCs, although other factors, such as bone marrow precursor or thymic damage, drug associated cytotoxicity, and suboptimal adherence to HAART, cannot be excluded in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␣ released per PDC in each sample was calculated as described earlier (10). Levels of proinflammatory cytokines TNF-␣ and IL-6 were measured using a protein biochip array system, Evidence Investigator (Randox laboratories), as described previously (35). Supernatants from cultures without TLR ligands were used as controls.…”
Section: Cytokine Analysismentioning
confidence: 99%
“…a number of independent studies and publications have been completed showing the validity of the randox evidence cytokine products. [38][39][40][41][42][43][44][45][46][47][48][49] the biochip array technology represents a highly standardized technique for cytokine and/ or cancer research. important and interesting at this point is the simultaneous determination of multiple analytes in a single patient sample, whereas elisas are limited to single analyte determinations per sample.…”
Section: Screening Performance Of Biomarkers Il-8 Vegf Ca 19-9 Andmentioning
confidence: 99%